The Mediterranean Sea and the Impact of Its Geographical Space and Cosmology upon Shakespeare’s Characters in Pericles - Neslihan Ekmekçioğlu (Ideas: Journal of English Literary Studies)
Multiple representations of space and geography in Pericles can be evaluated from different points of view. The sea in Pericles witnesses the nativity of Pericles’s child, Marina and the burial of his wife, Thaisa within a chest. The natural elements lead the casket in which Thaisa is buried to the shore of Ephesus. Thaisa can be thought as the treasure of the deep. Her casket is discovered after a turbulent and stormy night by Cerimon who brings her back to life. The remarks regarding the wondrous meteorological phenomenon of the tempest point to the symptoms of an earthquake which caused the billow, the swelling of the sea which delivered the chest of Thaisa’s supposedly dead body to the seacoast. All the sudden turns and unpredictable events display the life experiences of Pericles who wanders in the Mediterranean Sea for many years. Shakespeare’s maritime imagination reveals a profound ontological relationship between the sea and human maturation in the sense of reaching a higher level of humanity. The ocean with its tempests and shipwrecks mostly contributes to sudden shifts in human lives and brings a kind of transformation in the lives of Shakespeare’s characters. In Pericles, the Mediterranean Sea with the impact of its geographical space and cosmology brings hope and despair, life and death as well as changes in Pericles’s life. The sea also witnesses the revival of life with magic and music at the seashore of Ephesus. My paper will deal with the multi-faceted geographical space of the Mediterranean Sea and its impact on character development in Shakespeare’s Pericles.